Analysis Of The Role Of Farming Group In Increasing Corn Production - Kasmawati Kasmawati; Nurhapsa Nurhapsa; Nurhaeda Nurhaeda (Agribusiness Journal, 2023)
This study aims to analyze the role of farmer groups as learning classes, collaboration vehicles, production units, and business units in Lemoe Village, Bacukiki District, Parepare City. This research was conducted from 7 July 2023 to 7 August 2023 in Lemoe Village, Bacukiki District, Parepare City. This study uses primary data collection techniques and secondary data. The method used is descriptive analysis and Likert scale. The results showed that (1) Farmer groups played a very important role as a learning class for increasing corn production in Lemoe Village. (2) The role of farmer groups is very important as a media for cooperation in increasing corn production in Lemoe Village. (3) The role of farmer groups as a production unit plays a role in increasing the production of corn in Lemoe Village. (4) The role of farmer groups as a business unit plays a role in increasing corn production in Lemoe Village.